Residual Properties in Damaged Laminated Composites through Nondestructive Testing: A Review - Boursier Niutta, Carlo; Tridello, Andrea; Paolino, Davide S.; Belingardi, Giovanni (Materials, 2021)
The development of damage tolerance strategies in the design of composite structures constitutes a major challenge for the widespread application of composite materials. Damage tolerance approaches require a proper combination of material behavior description and nondestructive techniques. In contrast to metals, strength degradation approaches, i.e., the residual strength in presence of cracks, are not straightforwardly enforceable in composites. The nonhomogeneous nature of such materials gives rise to several failure mechanisms and, therefore, the definition of an ultimate load carrying capacity is ambiguous. Nondestructive techniques are thus increasingly required, where the damage severity is quantified not only in terms of damage extension, but also in terms of material response of the damaged region. Based on different approaches, many nondestructive techniques have been proposed in the literature, which are able to provide a quantitative description of the material state. In the present paper, a review of such nondestructive techniques for laminated composites is presented. The main objective is to analyze the damage indexes related to each method and to point out their significance with respect to the residual mechanical performances, as a result of the working principle of each retained technique. A possible guide for future research on this subject is thus outlined.